Design and Modal Analysis of a New Type Cycloidal Reducer with Movable Output-pins - Li Yang; Xu Lixin; Hou Changxing; Chang Le (Jixie chuandong)
A new precision cycloidal reducer with movable output-pins is proposed. Firstly, the transmission principle and structural characteristics of the cycloidal reducer with movable output-pins are explained, and the new cycloidal reducer is equipped with the movable output-pin mechanism, which can significantly improve the transmission efficiency of the reducer by changing the sliding friction between the output-pin and the pin-hole into rolling friction. Secondly, the static characteristics of key transmission components are calculated, and the effects of cycloidal tooth profile modification and pin-hole fit clearance on the cycloidal transmission meshing force and movable output-pin contact force are analyzed, respectively. Then, the modal characteristics of the reducer are analyzed based on the finite element technology and the inherent frequencies and vibration characteristics of each order of the reducer are obtained. Finally, the physical prototype of the cycloidal reducer with movable output-pins is manufactured and the transmission efficiency is tested, which provides an effective technical solution for the product innovation of industrial robot precision reducers.